2015
DOI: 10.1158/0008-5472.can-14-2356
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Pharmacological Screens Converge in Identifying FLIP, BCL2, and IAP Proteins as Key Regulators of Sensitivity to the TRAIL-Inducing Anticancer Agent ONC201/TIC10

Abstract: ONC201/TIC10 is a small molecule inducer of the TRAIL gene under current investigation as a novel anticancer agent. In this study, we identify critical molecular determinants of ONC201 sensitivity offering potential utility as pharmacodynamic or predictive response markers. By screening a library of kinase siRNAs in combination with a subcytotoxic dose of ONC201, we identified several kinases that ablated tumor cell sensitivity, including the MAPK pathway inducer KSR1. Unexpectedly, KSR1 silencing did not affe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 18 publications
(23 reference statements)
1
43
0
Order By: Relevance
“…27 This study investigated a subset of approved small molecules that were curated for NHL relevance. Our limited combinatorial study identified cytarabine as a synergistic combination with ONC201 in pediatric NHL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 This study investigated a subset of approved small molecules that were curated for NHL relevance. Our limited combinatorial study identified cytarabine as a synergistic combination with ONC201 in pediatric NHL.…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that ONC201 exhibits synergy with several approved targeted agents and chemotherapies that range from multikinase inhibitors, alkylating agents and inhibitors of DNA/ nucleoside synthesis. 27 We specifically examined the combinatorial efficacy of ONC201 with chemotherapies used to treat pediatric lymphoma (Fig. 4A).…”
Section: Onc201 Cooperates With Several Pediatric Lymphoma Chemotheramentioning
confidence: 99%
“…ONC201 has substantial antitumor activity in preclinical models in various advanced solid tumors with infrequent oral dosing and without toxicity in normal cells in culture and in vivo (12). Preclinical studies demonstrated broad synergism of ONC201 with established anticancer therapies, including the depletion of colorectal cancer stem cells (13, 14). …”
Section: Introductionmentioning
confidence: 99%
“…We also recently demonstrated potent antitumor effects on colorectal cancers initiated by cancer stem/progenitor cells (CSCs) (7). In vivo, first-in-class small molecule ONC201 exhibits a broad spectrum of anticancer activity, a wide safety margin, robust stability, aqueous solubility, blood-brain barrier penetration, and favorable pharmacokinetics (1)(2)(3)(4)(5)(7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%